The Influence of Gender Role and Women's Empowerment on Couples' Fertility Experiences in Urban Society of Mashhad, Iran - Talat Khadivzadeh; Robab Latifnejad Roudsari; Masoud Bahrami (Mashhad University of Medical Sciences, 2014)
Background and Aim: Iran has experienced a great variation in women's status in recent years. There is a little knowledge on how and why advancing gender equality and equity and the empowerment of women play a role in recent fertility reduction in the country. This study was conducted to gain insight into the role of gender beliefs and women's empowerment in the couples 'experiences of fertility in Mashhad, Iran in 2011-2012. Methods: In this exploratory qualitative study in-depth interviews were conducted with 54 purposefully selected eligible male and female participants and some key informants who lived in urban society of Mashhad. Data was collected until saturation was happened and analyzed adopting conventional content analysis approach through giving analytical codes and identification of categories using MAXqda software. Study rigor verified via prolonged engagement, thick description and validation of anlysis through member check. Results:Findings from data analysis demonstrated three major categories about the influence of women's empowerment and gender role on fertility experiences including: 1) The couple's understanding of gender roles 2) Women's empowerment and changing gender roles 3) Couple's interactions in complementary or parallel roles and 4) Fulfillment of fertility goals based on role division. Some aspects of couples' interaction including equal roles in fertility decisions, choosing and using best fit family planning method and participative child care influenced couples' fertility behavior. Women's empowerment together with balanced gender role in the family resulted in success in attaining couple's fertility desire. Conclusion: Managing fertility behaviors needs to understand the roles of spouses in their mutual interaction in fertility decision making and related behaviors. Imbalanced gender role in family acts as an obstacle to reach the fertility goals and leads to lower than desired fertility. Reproductive health policy makers and family planning counselors could apply the findings of this study in order to publicize proper fertility behaviors through making the couples aware of the risks of gender role imbalance.